Solr 1.4 enterprise search server : enhance your search with faceted navigation, result highlighting, fuzzy queries, ranked scoring, and more /: enhance your search with faceted navigation, result highlighting, fuzzy queries, ranked scoring, and more. (2009) - Unknown
No abstract available